Climate change impacts in Bhutan: challenges and opportunities for the agricultural sector - Parker, Louis; Guerten, Nora; Nguyen, Than Thi; Rinzin, Chimi; Tashi, Dawa; Wangchuk, Dorji; Bajgai, Yadunath; Subedi, Kiran; Phuntsho, Loday; Thinley, Namgay; Chhogyel, Ngawang; Gyalmo, Tasho; et al. (2017)
The Kingdom of Bhutan is nestled in the Himalayas, sharing borders with India to the south and China to the north. The country is a net carbon sink and has committed to ensuring that 60% of its total land area will remain as forest. Despite efforts to encourage sustainable economic growth at the national level, the impacts of climate change, driven partly by the global greenhouse gas emissions, will continue to affect Bhutan. The agricultural sector, which employs about 69% of the total population, is the most vulnerable to the changing climate. There is need to identify which crops may become unsuitable under climate projections and, equally, which crops may offer new opportunities to rural communities. A joint study by the International Center for Tropical Agriculture (CIAT) and the Ministry of Agriculture and Forestry (MoAF), funded by the United Nations Environment Programme (UNEP), was undertaken to assess the impacts of climate change on five key crops (i.e. rice, maize, potato, chili and tomato) and three diversification crops (i.e. quinoa, kiwi and cardamom). The results of the study will help decision makers identify which areas may require interventions due to the imminent loss of climate suitability for the crops. Equally, the results can be used to provide input on suitable locations to test the diversification crops and potential areas for expansion of the key crops. The analysis was undertaken using the most up-to-date climate models and an ecological niche model and was analyzed in ArcGIS. It was a collaborative study, which included a 2-week capacity building workshop between CIAT and MoAF and an additional case study to integrate knowledge on gender and climate change.